A study on the relationship between momentum strategies and firm size. - Tan, Hong Thai. (2010)
Momentum strategies have attracted a widespread following ever since they were documented by Jegadeesh and Titman (1993). This study targets the momentum effect under a more relevant context from 1983 to 2008 in the American stock markets. We proved that the momentum effect exist in our period studied and its sub-periods of bull and bear markets by replicating the methodology in Jegadeesh and Titman (1993). We observe that momentum returns are directly related to market capitalization, which is contrary to the findings of the firm size effect. There is also a significant difference in momentum returns under the effect of dividends and this reveals the possibility that there was a downward bias in the positive momentum profits originally documented by Jegadeesh and Titman (1993). In addition, the profitability of a momentum strategy is brought under question in lieu of the marginal momentum returns found under this study.